ECONOMIC SECURITY IN THE FORMATION AND DEVELOPMENT OF PRODUCTION INDUSTRY CLUSTERS: THEORETICAL REVIEW (Marketing Journal, 2025)
The article examines economic security in the formation and development of clusters of the manufacturing industry. Clusters are an association of interconnected enterprises, scientific institutions and infrastructure facilities, which contributes to increa sing the competitiveness and sustainability of the economy. However, without effective mechanisms for ensuring economic security, clusters may face risks that affect their development.
Keywords: economic security; resource provision; national security; measures to ensure the economic security of industrial clusters; functioning and development of industrial clusters